Current surgical management of metastatic pathological fractures of the femur: A multicentre snapshot audit. Issue 8 (August 2020) - Rai, Paul; Aziz, Sheweidin; Kannan, Sudhir; Ashford, Robert; ,; Aziz, Sheweidin; Mitchell, Lara; Brown, Andrew; Hutchings, Steffan; Rai, Paul; Hau, Melinda; Howard, Dan; et al.
Abstract: Aims: We aimed to find out: the typical workload for metastatic bone disease, the conventional treatment for femoral metastases and whether there is a trend for arthroplasty and endoprosthetic reconstruction. Materials and methods: All sequential patients undergoing surgery for femoral metastatic lesions (both pathological fracture and impending pathological fracture) of any age patient were included in the multicenter snapshot audit. Data on demographics, institutions and operative procedures were recorded. Results: 24 UK Institutions were enrolled, including 7 Major Trauma Centres (MTCs). It was a 2 month audit from 1 st March 2018. 95 cases were recorded. The mean age was 71 and 65% were female. 66 patients had a fracture at presentation and 23 an impending fracture. Breast carcinoma was the primary tumour at 23%. The mean Mirel's score is 9. The commonest fixation was with a long cephalomedullary nail (38%). Endoprostheses accounted for 24%. None of the endoprostheses were implanted at MTCs. Conclusion: This audit revealed large numbers of cases of femoral metastases. Although the use of endoprostheses may be increasing in Trauma Units, intramedullary nailing still predominates. Future pathways may benefit from directing resources to allow greater arthroplasty.